Parent Feedback on the Reducing Emotional Distress for Childhood Hypoglycemia in Parents (REDCHiP) Intervention: A Qualitative Analysis - Nicole A. Kahhan; MaryJane S. Campbell; Mark A. Clements; Kimberly A. Driscoll; Amy I. Milkes; Holly K. O’Donnell; Susana R. Patton (Children)
Objectives: Severe hypoglycemia is more common among young children with type 1 diabetes mellitus (T1DM) than older youth, and parents report significant hypoglycemia fear (HF). Parents experiencing HF describe constant and extreme worry about the occurrence of hypoglycemia and may engage in potentially risky behaviors to avoid hypoglycemia. Our team developed and tested a behavioral intervention, Reducing Emotional Distress for Childhood Hypoglycemia in Parents (REDCHiP), to decrease HF in parents of young children with T1DM. Here, we qualitatively analyzed parent feedback to refine and optimize future intervention iterations. Methods: The randomized pilot study included parents (n = 73) of young children with T1DM who participated in the 10-session video-based intervention. We qualitatively analyzed 21 recordings of the final intervention session, where parents provided feedback about intervention content. Trained coders independently reviewed each session. The frequency of parent quotes regarding active REDCHiP treatment components were calculated. Results: The coded themes reflected active treatment components [viz., Use of Cognitive Behavioral Therapy (CBT) Skills, Coping, Behavioral Parenting Strategies]. Also, two secondary process codes were identified: Appreciate REDCHiP Content and Challenges in Applying REDCHiP Strategies. Parents provided examples of skills or concepts they applied from REDCHiP, the challenges they encountered, and if they planned to apply these skills in the future. Conclusions: A qualitative analysis provided insight into parent perceptions of the active treatment components within the REDCHiP intervention, their acceptability, and parents’ intention to apply REDCHiP skills/concepts within daily T1DM cares. Future iterations of the intervention that trial alternative formats (i.e., individual vs. group and asynchronous vs. telehealth) may increase accessibility and scalability.